Trends in awareness and uptake of genetic testing among the United States population, 2011–2022 - Ariana Naaseh; Mengyao Shi; Steven Tohmasi; Erin L. Linnenbringer; Julie A. Margenthaler; Graham A. Colditz; Yin Cao (Journal of Community Genetics, 2026)
While genetic testing (GT) has become more available over the past decade, it is unclear whether public awareness and use have increased proportionally. We aimed to evaluate national trends in GT awareness and usage. We performed a cross-sectional analysis of nationally representative data from the National Cancer Institute’s Health Information National Trends Survey (HINTS). We analyzed survey responses from HINTS 4 Cycle 1–4 (2011–2014), 5 Cycle 1 and 4 (2017, 2020), and 6 (2022). Primary outcomes were overall genetic testing awareness and uptake. Secondary analyses evaluated awareness and uptake of health-related genetic testing (e.g. disease risk, cancer, and carrier testing) among survey cycles in which specific testing modalities were available. Linear regression assessed crude trends and multivariable logistic regression estimated odds ratios (OR). Among 22,256 respondents, overall awareness of GT increased from 36.6% in 2011 to 81.7% in 2022 (trend p < .001). Awareness was lower among individuals who were older (e.g., ref: age 18–34 , age 75+: OR 0.53 , 95% confidence interval [CI]: 0.43–0.64 ), male ( ref: female , OR 0.85 , CI: 0.77–0.95 ), non-Hispanic Black ( ref: non-Hispanic White , OR 0.63 , CI: 0.54–0.74 ), non-Hispanic Asian ( ref: non-Hispanic White , OR 0.38 , CI: 0.29–0.48 ), Hispanic ( ref: non-Hispanic White , OR 0.60 , CI: 0.52–0.69 ), with less than a college education (e.g., ref: some college , less than high school: OR 0.60 , CI: 0.47–0.77 ), and with annual household income <$75,000 (e.g., ref: >$75 , 000 , <$20 , 000: OR 0.49 , CI: 0.42–0.59 ). GT uptake increased from 21.4% in 2020 to 35.6% in 2022 (trend p < .001). GT uptake was lower among individuals who were non-Hispanic Asian ( ref: non-Hispanic White , OR 0.60 , CI: 0.38–0.96 ) and had household incomes <$35,000 (e.g., ref: >$75 , 000 , <$20 , 000: OR 0.68 , CI: 0.49–0.94 ), but higher among those with a personal history of cancer ( ref: no cancer history , OR 1.44 , CI: 1.07–1.92 ). Although GT awareness has grown, there are notable gaps across sociodemographic groups. Further study should better characterize factors influencing health-related GT uptake patterns.